Las categorías de productos como base para la elaboración de estrategias exitosas ed el comercio electrónico B2C - I. Borraz Mora; Lucio Fuentelsaz Lamata; Yolanda Polo Redondo (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
The Internet and electronic commerce have entailed a revolution for society and businesses. However, it has been observed that all products have not the same probability of success due to its particular features. Thus, knowing how firms have to marketing their products through the Internet has become a key question. As a result, the main objectives of this paper are both, elaborating a consistent classification of product categories and proposing successful strategies for it. This research shows the relevance of two variables in order to reach our purposes: the difficult to evaluate a product and consumer perceived risk.
Keywords: 330; business to consumer (B2C) electronic commerce; business success; product categories